PSYCHOLOGICAL AND PEDAGOGICAL SUPPORT OF SPORTS ACTIVITIES FROM GAMES IN THE CONTEXT OF PERSONALITY SELF REALIZATION (Physical Culture and Sport: Scientific Perspective, 2023)
Underestimation of the role of the personal factor in the system of training athletes, the lack of an individual approach to each athlete, is the cause of low success and the problems that arise. The psychological support of the athlete is aimed at the harmonious development of the athlete's personality in the chosen sport, the reduction of erroneous actions for the formation of movement programs.From a psychological and pedagogical point of view, sports activity is one of the spheres of activity in which abilities and their formation play a determining role in the athlete's achievements, as well as a multi-year systematic continuous process of training and physical development. An important qualitative characteristic of the level of development of an athlete's abilities is the health culture of his personality. Only with the development of social activities is it possible to increase and improve the level of improvement in all spheres of an athlete's life. But at the same moment, there is a desire to develop a certain type of activity in oneself, but also to try to carry it out. This can be called the main direction in the development of a modern competitive culture of the individual.Psychological support is a set of measures to increase the effectiveness of all types of training of an athlete and, first of all, to ensure mental readiness for performance, creating prerequisites for a long sports career and stable demonstration of high results. Only a deep analysis of the features of sports training and the mechanisms of influence on the psyche, the selection of adequate forms and means of training, the interaction of all participants in the training process will allow the athlete's potential to be fully realized and maintain a high level of competitive achievements.
Keywords: psychology; pedagogical control; sports; personality development; physical development